Global mtDNA genetic structure and hypothesized invasion history of a major pest of citrus, Diaphorina citri (Hemiptera: Liviidae). Issue 1 (26th November 2017) - Luo, Yufa; Agnarsson, Ingi
Abstract: The Asian citrus psyllid Diaphorina citri Kuwayama is a key pest of citrus as the vector of the bacterium causing the "huanglongbing" disease (HLB). To assess the global mtDNA population genetic structure, and possible dispersal history of the pest, we investigated genetic variation at the COI gene collating newly collected samples with all previously published data. Our dataset consists of 356 colonies from 106 geographic sites worldwide. High haplotype diversity (H‐mean = 0.702 ± 0.017), low nucleotide diversity (π‐mean = 0.003), and significant positive selection (Ka/Ks = 32.92) were observed. Forty‐four haplotypes (Hap) were identified, clustered into two matrilines: Both occur in southeastern and southern Asia, North and South America, and Africa; lineages A and B also occur in eastern and western Asia, respectively. The most abundant haplotypes were Hap4 in lineage A (35.67%), and Hap9 in lineage B (41.29%). The haplotype network identified them as the ancestral haplotypes within their respective lineages. Analysis of molecular variance showed significant genetic structure ( F ST  = 0.62, p  < .0001) between the lineages, and population genetic analysis suggests geographic structuring. We hypothesize a southern and/or southeastern Asia origin, three dispersal routes, and parallel expansions of two lineages. The hypothesized first route involved the expansion of lineage B from southern Asia into North America via West Asia. The second, the expansion of some lineage A individuals from Southeast Asia into East Asia, and the third involved both lineages from Southeast Asia spreading westward into Africa and subsequently into South America. To test these hypotheses and gain a deeper understanding of the global history of D. citri, more data‐rich approaches will be necessary from the ample toolkit of next‐generation sequencing (NGS). However, this study may serve to guide such sampling and in the development of biological control programs against the global pest D. citri . Abstract : The Asian citrus psyllid Diaphorina citri Kuwayama is a key pest of citrus as it is the vector of the bacterium that causes the "huanglongbing" disease (HLB). To determine global population genetic structure, and evaluate dispersal history of the pest, we investigated its genetic variation at the mitochondrial COI gene collating newly collected samples with all previously published data. In total, our dataset consists of 356 colonies from 106 geographic sites worldwide. Our data may be important to the development of biological control programs against the global pest D. citri .